Biofilm Formation and Synthesis of Antimicrobial Compounds by the Biocontrol Agent Bacillus velezensis QST713 in an Agaricus bisporus Compost Micromodel - Pandin, Caroline (Appl Environ Microbiol, 2019)
Bacillus velezensis QST713 is widely used as a biological control agent for crop protection and disease suppression. This strain is used industrially in France for the protection of Agaricus bisporus against Trichoderma aggressivum f. europaeum, which causes green mold disease. The efficacy of this biocontrol process was evaluated in a previous study, yet the mode of its action has not been explored under production conditions. In order to decipher the underlying biocontrol mechanisms for effective biofilm formation by strain QST713 in the compost and for the involvement of antimicrobial compounds, we developed a simplified micromodel for the culture of A. bisporus during its early culture cycle. By using this micromodel system, we studied the transcriptional response of strain QST713 in the presence or absence of A. bisporus and/or T. aggressivum in axenic industrial compost. We report the overexpression of several genes of the biocontrol agent involved in biofilm formation in the compost compared to their expression during growth in broth compost extract either in the exponential growth phase (the epsC, blsA, and tapA genes) or in the stationary growth phase (the tapA gene), while a gene encoding a flagellar protein (hag) was underexpressed. We also report the overexpression of Bacillus velezensis QST713 genes related to surfactin (srfAA) and fengycin (fenA) production in the presence of the fungal pathogen in the compost. IMPORTANCE Biocontrol agents are increasingly used to replace chemical pesticides to prevent crop diseases. In the button mushroom field in France, the use of Bacillus velezensis QST713 as a biocontrol agent against the green mold Trichoderma aggressivum has been shown to be efficient. However, the biocontrol mechanisms effective in the Agaricus bisporus/Trichoderma aggressivum/Bacillus velezensis QST713 pathosystem are still unknown. Our paper focuses on the exploration of the bioprotection mechanisms of the biocontrol agent Bacillus velezensis QST713 during culture of the button mushroom (Agaricus bisporus) in a micromodel culture system to study the specific response of strain QST713 in the presence of T. aggressivum and/or A. bisporus.